Studi Kasus Konseling Pastoral terhadap Remaja pada Keluarga yang tidak Harmonis - Kalensang, Geby Ladesya (PT. Giat Konseling Nusantara, 2024)
The aim of this research is to find out and describe the condition of teenagers in disharmonious families in living their daily lives, the impact of disharmonious families on teenagers. Moreover, what are the appropriate counseling approaches and techniques for these teenagers. In this research, the method that will be used is qualitative research using the Pastoral Case Study Method which was carried out at GMIST Torsina Winangun Congregation. The theory used in this research is pastoral, youth and family counseling. The results of the analysis that the researchers obtained from this research showed that a disharmonious family between the subject's parents had an impact on the subject's behavior, including consuming alcohol, smoking, distancing himself from fellowship, and dropping out of school. This case has occurred but the church has not yet paid attention to it, its services for problems like this are still lacking